Assessing Creativity in Hollywood Pitch Meetings: Evidence for a Dual-Process Model of Creativity Judgments - Elsbach, Kimberly D.; Kramer, Roderick M. (Academy of Management Journal, 2003)
This study addresses an important but neglected topic by investigating the social judgment processes that experts (studio executives and producers in Hollywood) use to assess the creative potential of unknown others (relatively unknown screenwriters) during ?pitch? meetings in which screenwriters attempt to sell their ideas. The findings suggest a dual-process social judgment model. In one process, person categorization, the experts used behavioral and physical cues to match ?pitchers? with seven creative and uncreative prototypes. In another process, relationship categorization, the experts used relational cues and self-perceptions to match pitchers with two relational prototypes.